THE EFFECT OF GREEN TEA (Camellia sinensis) EXTRACT ON THE THICKNESS OF BRONCHIAL EPITHELIUM AND PULMONARY ARTERY WALL OF MICE (Mus musculus) EXPOSED TO CIGARETTE SMOKE - Rahmatullah, Aldin Akbar (VITEK : Bidang Kedokteran Hewan, 2024)
The study aims to investigate the impact of green tea extract on the thickness of bronchial epithelium and pulmonary artery walls in mice lungs exposed to cigarette smoke. Twenty-five 12-week-old mice (Mus musculus) weighing between 20-25 grams were used in the experiment. The control group (K(-)) received no cigarette smoke exposure and was administered 0.5 mL of 1% Na-CMC, while the positive control group (K(+)) was exposed to cigarette smoke without green tea leaf extract and received 0.5 ml of 1% Na-CMC. Groups exposed to cigarette smoke (P1, P2, and P3) were given green tea extract at doses of 20 mg/kgBW, 40 mg/kgBW, and 60 mg/kgBW respectively, each in a daily dose of 0.5 ml. Mice were exposed to one cigarette per group per day. The findings indicate that administering green tea extract has the potential to reduce the thickening of both the bronchial epithelium and pulmonary artery walls, with the optimal dose being 40 mg/kgBW. Analysis using ANOVA revealed significant differences in the thickness of the bronchial epithelium and pulmonary artery walls among the groups (p < 0.05). This study demonstrates that administering green tea extract suspension (Camellia sinensis) can effectively mitigate the thickening of the bronchial epithelium and pulmonary artery walls in mice lungs exposed to cigarette smoke.